The big book of team-building games: trust-building activities, team spirit exercises, and other fun things to do - Newstrom, John W.; Scannell, Edward E. (Paris, 1998)
"Did you know that games can be a terrifically effective way to build team spirit, communication, and trust among people who work together day in and day out? Now you can spark morale in any work group by choosing from 70 stimulating games and activities specifically designed for the manager who's looking to raise sagging morale in a department, liven up boring staff meetings, enable team members to collaborate smoothly and effectively, and much more!"